Qualitative Training and its Impact on Some Biomechanical Indicators of the Triple Jump – Youth - Mohammed, Saif; Hussein, Ihab (Journal of Physical Education, 2020)
This study aimed to prepare a qualitative training according to the stages of triple jump and to identify the effect of such exercises on some biomechanical indicators for triple jump stages, while the researchers assumed that there were significant differences between the pre and post tests in some biomechanical indicators for the effectiveness triple jump stages, and for the post test The study was applied on a sample consisting of 6 and athlete’s representing the National Center for Sports Talent in Baghdad their average age was (18.7) (±0.971) years, their average lengths was (179.5)(±5.502)cm, and their average weights (66.4)(±5.027)kg, researchers used the experimental method of one group, and the biomechanical indicators of the study were measured by using video imaging at a speed of (240 images/sec) and for all stages of the activity, as specific training was applied over a period of (8) weeks at a rate of (24) (Training unit, distributed on (3) units a week, as these exercises were within the main section of the training unit within the period of special preparation, and after the researchers used the statistical means, the researchers came out with the emergence of an improvement in biomechanical indicators and for all stages of competition